Customer Trust as a Mediator of eWOM, Brand Trust, and Promotion on Online Purchase Intention: A Study of Skintific Products on TikTok Shop, Indonesia - Vanesya Auliya Putri Awalupi; Edy Purwo Saputro (Institute of Computer Science (IOCS), 2026)
This study investigates the influence of Electronic Word of Mouth (EWOM), Brand Trust, and Promotion on consumers’ interest in online purchases, with Customer Trust as a mediating variable, focusing on Skintific products on TikTok Shop in Indonesia. While previous studies have examined online purchase behavior, limited research has explored the simultaneous roles of EWOM, Brand Trust, and Promotion in the context of short-video social commerce platforms. Using a quantitative approach, data were collected from 435 students in Surakarta via purposive sampling and structured Likert-scale questionnaires, complemented by secondary sources for contextual understanding. Analysis was performed using SmartPLS software, applying multiple linear regression and Sobel tests to evaluate both direct and indirect relationships. Validity and reliability were confirmed through Pearson correlation and Cronbach’s alpha, with classical assumption tests ensuring regression robustness. Results show that EWOM positively affects Brand Trust but not Promotion perception, while Customer Trust significantly strengthens both Brand Trust and responsiveness to Promotion. Transparent and attractive Promotions further enhance Brand and Customer Trust, ultimately increasing online purchase interest. This study contributes to the literature by highlighting the mediating role of Customer Trust in short-video social commerce and providing practical strategies for brands to leverage EWOM and Promotions to drive online purchasing behavior.